The principles of analysis of competitiveness and control schemes in transport services - Žvirblis, Algis (Transport, 2003)
Under the conditions of constantly growing competition Transportation companies are faced with theoretical and practical problems associated with the quality and stability of transport services, competitiveness on the market and marketing problems. Road transport services are considered in the terms of value analysis while the assessment of their competitiveness is based on the Pontriagin maximum principle. A model for transport risk analysis is constructed, taking into account the principles of correlation and co -variation of transport services. Formalized models of automated control of services in the system of marketing allowing the analysis of stability and other parameters to be made in the framework of automatic control theory are offered. First Published Online: 19 Dec 2011